Visceral Leishmaniasis Turning into Chronic Liver Disease (Journal of Medicine, 2016)
Kala-azar and chronic liver disease are conditions frequently seen in our country. In some instances, when features of both diseases co-exist, it may pose as a diagnostic dilemma. We intend to report a case here, where presence of such features led to much confusion.J MEDICINE January 2016; 17 (1) : 51-54